FELIPE II, HIS EMPIRE, HIS WIVES AND LOVERS - HELGA Hediger (Ибероамериканские тетради, 2016)
The article is dedicated to some events of the personal history of Felipe II, so discussed by the historians of his time and modern scientists, who try to rehabilitate his image